Penerapan Metode Pemodelan untuk Menigkatkan Kemampuan Menulis Puisi Siswa Kelas IV SD Inpres 2 Bantaya - Larate, Abdullah (Bahasantodea, 2016)
Based at the first reflection outcomes that have done by the researcher in the SD Inpres 2 Bantaya, it founded the information that the student ability in the writing poetry still have low. The indicator founded that the scores average of the students was 60 scores. Whereas, the minimal completeness achieved score was 70 scores. The students have the difficult to expresses their mind and feelling in the poetry form. This research focussed to increasing poetry writing ability at the fourth grade student of SD Inpres 2 Bantaya with using modelling method, the problem statement in this research is how to applicate the modelling method to increasing poetry writing ability at the fourth grade student of SD Inpres 2 Bantaya with using modelling method. The nstrument that used to supports this research are : (1) first observation sheet (2) Observation sheet, (3) Reflection sheet, (4) Interview sheet, (5) Evaluation Sheet. Based on the finding and research outcomes that have done at the cycle I (53,46%) at the first meeting and (63,33%) at the second meeting. The implementation in the cycle II, the first meeting achieve (76,01%), and the second meeting achieve (86,33%). It is show that modelling method was effective to increasing poetry writing ability at the sixth grade student of SD Inpres 2 Bantaya.